Deformation of elastomeric chains related to the amount and time of stretching - Yagura,Denise (2013)
OBJECTIVE: To investigate a potential relationship between degree of stretching and resulting permanent deformation of elastomeric chains (ECs) as well as whether or not stretching time has any bearing on the degree of permanent deformation. METHODS: Five-module segments of closed elastomeric chains manufactured by 3M Unitek were stretched to 10-100% of their original length in devices especially designed for this purpose, remaining submerged in artificial saliva at 37 ± 1° C and were removed sequentially after 1, 2, 3 and 4 weeks. Upon removal, each segment was measured and, once recorded the values, were statistically analyzed with the purpose of assessing the degree of permanent deformation. CONCLUSIONS: It was concluded that permanent deformation is directly proportional to the degree of stretching of the ECs assessed. The mean percentages found were 8.4% to 10% of stretching, and exceeding 20% (21.3%) when stretched by 40%, and reaching 56.6% permanent deformation when stretched 100% of their original length. Finally, the highest percentage of permanent deformation occurred during the first week and was not statistically significant after this period.